2017
DOI: 10.3390/ijms18091868
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells: Angels and Devils for Immunotherapy

Abstract: In recent years, the relevance of the immune system to fight cancer has led to the development of immunotherapy, including the adoptive cell transfer of immune cells, such as natural killer (NK) cells and chimeric antigen receptors (CAR)-modified T cells. The discovery of donor NK cells’ anti-tumor activity in acute myeloid leukemia patients receiving allogeneic stem cell transplantation (allo-SCT) was the trigger to conduct many clinical trials infusing NK cells. Surprisingly, many of these studies did not ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 116 publications
(145 reference statements)
0
65
0
Order By: Relevance
“…As aforementioned, NK cells can also exhibit potent anti-tumor function and their activity is modulated by an array of inhibitory and activating receptors [198]. Because of their cytotoxic capacity, a few studies have also examined the potential of NK lymphocytes to serve as a cellular platform for CARs (reviewed in [336]).…”
Section: Looking For the Best Cell To Engineermentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, NK cells can also exhibit potent anti-tumor function and their activity is modulated by an array of inhibitory and activating receptors [198]. Because of their cytotoxic capacity, a few studies have also examined the potential of NK lymphocytes to serve as a cellular platform for CARs (reviewed in [336]).…”
Section: Looking For the Best Cell To Engineermentioning
confidence: 99%
“…NCR ligands can also regulate the receptor function and may facilitate tumor escape from NK cells [195][196][197], which would support their extensive expression by tumor cells. Although usage of NK-based immunotherapies is currently limited by poor expansion and endogenous inhibitory mechanisms [198], one way to combine the tumor recognition capability of NK cells with T cell effectiveness and flexibility is to design CARs based on the EC domain of NCRs. Thus, we and others showed that NCR1 [199], NCR2 [105] and NCR3 [200] based chimeric receptors can mediate the recognition of several types of tumors (e.g.…”
Section: Using Nk Receptors To Bridge Between Innate and Adaptive Immmentioning
confidence: 99%
“…Although PD-1 antibodies, including pidilizumab, lambrolizumab, and nivolumab mainly target T cells and provide tumor suppression, they also may boost endogenous NK cell functions [51]. NK cell cytotoxicity can also be enhanced and redirected to tumor cells via bi-or tri-specific engagers [52][53][54]. These monoclonal antibodies may be combined with other treatments, particularly NK-stimulating cytokines, in order to produce synergistic effects.…”
Section: Effects Of Specific Monoclonal Antibodies and Immune Checkpomentioning
confidence: 99%
“…Unlike neutrophils and suppressor populations of myeloid cells, whose contribution to the progression of solid tumors has only recently come under intense investigation, the functions of natural killer cells have always been considered in the context of cancer immunosurveillance. However, in spite of the fact that for this group of innate lymphoid cells, a detailed spectrum of receptors allowing for recognition of transformed cells has been described and a vast diversity of mechanisms for their cytotoxic action has been established, attempts to use them in anticancer therapy occurred to be unsuccessful-the reasons for this situation are reviewed in [41], and among these reasons are the underappreciated regulatory properties of NK cells implementing via production of a wide range of cytokines, the specificity of which is largely determined by the surrounding molecular context. Nevertheless, recently there has been considerable revival of interest in NK cells brought about by the invention of chimeric antigen receptors (CAR) technology that made possible creation of engineered CAR-NKs with "improved" properties (e.g., increased migrating and proliferating ability, up-regulated expression of activating receptors) for their subsequent adoptive transfer into a cancer patient.…”
Section: Sting Mrna Expression In Peripheral Blood Mononuclear Cells mentioning
confidence: 99%